Analisis Penggunaan Bahasa Indonesia pada Mahasiswa Jurusan Biologi Universitas Negeri Medan - Puteri, Anggia; Sinabutar, Novi K.; Putri, Aulia I.; Ambarwati, Tia; Aulya, Nury; Dani, Cut A. K.; Akbar, Habil; Oktavia, Arnis T. (CV. ITTC INDONESIA, 2024)
The effectiveness of using Indonesian as a means of communication and providing information. Good Indonesian is words that are suitable for communicating effectively. With language, a person can express ideas, ideas, thoughts and desires in conveying an opinion. Which aims to improve how to speak Indonesian properly and correctly. The application of Indonesian in daily life can be used as a weapon to develop an attitude of nationalism and unify all people in Indonesia. This research used qualitative methods by conducting interviews with students of the Biology Department, Medan State University. From the results of interviews with students from the Biology Department, Medan State University, it was said that students used good and correct Indonesian when together with lecturers, but outside of lectures, students from the Biology Department at Medan State University used current slang and their regional language. Therefore, we need to apply good and correct use and understanding of Indonesian every day so that Indonesian is not replaced by Modern language which is now very popular with young people.